Enhancing flowering plant functional richness improves wild bee diversity in vineyard inter‐rows in different floral kingdoms. Issue 12 (4th May 2021) - Kratschmer, Sophie; Pachinger, Bärbel; Gaigher, René; Pryke, James S.; van Schalkwyk, Julia; Samways, Michael J.; Melin, Annalie; Kehinde, Temitope; Zaller, Johann G.; Winter, Silvia
Abstract: Wild bees are threatened by multiple interacting stressors, such as habitat loss, land use change, parasites, and pathogens. However, vineyards with vegetated inter‐rows can offer high floral resources within viticultural landscapes and provide foraging and nesting habitats for wild bees. Here, we assess how vineyard management regimes (organic vs. conventional; inter‐row vegetation management) and landscape composition determine the inter‐row plant and wild bee assemblages, as well as how these variables relate to functional traits in 24 Austrian and 10 South African vineyards. Vineyards had either permanent vegetation cover in untilled inter‐rows or temporary vegetation cover in infrequently tilled inter‐rows. Proportion of seminatural habitats (e.g., fallows, grassland, field margins) and woody structures (e.g., woodlots, single trees, tree rows) were used as proxies for landscape composition and mapped within 500‐m radius around the study vineyards. Organic vineyard management increased functional richness (FRic) of wild bees and flowering plants, with woody structures marginally increasing species richness and FRic of wild bees. Wild bee and floral traits were differently associated across the countries. In Austria, several bee traits (e.g., lecty, pollen collection type, proboscis length) were associated with flower color and symmetry, while in South African vineyards, only bees' proboscis length was positively correlated with floral traits characteristic of Asteraceae flowers (e.g., ray–disk morphology, yellow colors). Solitary bee species in Austria benefitted from infrequent tillage, while ground nesting species preferred inter‐rows with undisturbed soils. Higher proportions of woody structures in surrounding landscapes resulted in less solitary and corbiculate bees in Austria, but more aboveground nesting species in South Africa. In both countries, associations between FRic of wild bees and flowering plants were positive both in organic and in conventional vineyards. We recommend the use of diverse cover crop seed mixtures to enhance plant flowering diversity in inter‐rows, to increase wild bee richness in viticultural landscapes. Abstract : This article studies how wild bee and plant diversity and functional traits are related to vineyard management intensities and viticulture landscape properties in Austria and South Africa. Common denominators for wild bees and flowering plants are studied across countries. Unique characteristics of the bee and plant communities in the vineyards of the two countries are analyzed using functional traits to provide subtlety conservation measures for wild bees in viticultural agroecosystems.